Faktor-Faktor yang Mempengaruhi Loyalitas Pelanggan Shopee di Mojokerto pada Masa Pandemi - Tiara Ajmi Rissalah; Lisa Sulistyawati (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
This study aims to 1) to determine and analyze the effect of satisfaction, service quality and price on customer loyalty, 2) to determine and analyze the effect of satisfaction on customer loyalty, 3) to determine and analyze the effect of service quality on customer loyalty, 4) to determine and analyze the effect of price on customer loyalty. The population in this study are Shopee customers in Mojokerto who are limited by certain criteria. The sample used in this study was 100 respondents using a non-probabilistic sampling technique with a purposive sampling approach. Collecting data in this study using a questionnaire via google form. The data testing methods used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, F Test and T Test. Based on the results of the study, it can be seen that satisfaction, service quality, and price simultaneously have a significant effect on customer loyalty. Satisfaction partially has a significant effect on customer loyalty. Service quality partially has a significant effect on customer loyalty. Price partially has a significant effect on customer loyalty.